Investigation of Different Affiliations of Shahid Beheshti University of Medical Sciences in Scientific Publications and Their Effect on the Result of Research Activities Evaluation - Azam Shahbodaghi; Shadi Asadzandi; Maryam Shekofteh; Farid Zayeri; Mostafa Rezaei Tavirani (Tehran University of Medical Sciences, 2016)
Background and Aim: Heterogeneous insertion of Organizational affiliations can cause loss of ranking points in the national and international levels. So, we decided to investigate the different affiliations of Shahid Beheshti University of Medical Sciences in scientific publications that indexed in Web of Science and their effect on the result of research activities evaluation in the year 2012. Materials and Methods: Methodology of this study is bibliometric approach with descriptive survey. The study included 1139 scientific production of Shahid Beheshti University of Medical Sciences that indexed in Web of Science in the first one in April 2011 to April 2012.  Results: 1139 articles indexed in the Web of Science, 94/38% in the evaluation of the research activities of the ministry of health have been scored and 5/61% failed. Among the unsuccessful papers 1/01%, had been inserted affiliation incorrectly. One-sample t-test showed that the mean score of 1/01% has no significant statistical impact on the total average rating of products indexed in Web of Science. Conclusion: Investigation showed that standard insertion of affiliation has impact on enterprise University Ranked and University status at the international level.